The Effects of Aging Time on Eating Quality of Semimembranosus Steaks - Samuel F. Stickley; Lauren M. Frink; Stephanie L. Witberler; Mason J. Prester; Jerrad F. Legako; Dale R. Woerner; Rhonda K. Miller; Chris R. Kerth; Mahesh N. Nair; Jessica M. Lancaster; Erin S. Beyer; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this study was to evaluate consumer palatability, instrumental tenderness, and objective color of semimembranosus steaks aged 14 to 70 days. Study Description: Beef semimembranosus subprimals were aged for 14, 28, 35, 42, 49, 56, 63, and 70 days, then cut into 1-in steaks. Color readings were taken before and after cooking. Steaks were cooked to 160°F then analyzed by consumers for overall liking, flavor, juiciness, and tenderness liking and acceptability. Color readings were used to calculate the percentage of oxymyoglobin (OMb), deoxymyoglobin (DMb), metmyoglobin (MMb), chroma, and hue angle. Warner-Bratzler Shear Force (WBSF) tests were conducted. Results: Consumer sensory results showed 28, 56, and 70 day steaks rated higher (P < 0.05) for tenderness and overall liking scores compared to 14 day steaks. There was also a higher (P < 0.05) percentage of 70 day steaks rated as acceptable for tenderness compared to 14 day steaks. There were no other sensory differences (P > 0.05) found for flavor liking and juiciness liking. Moreover, WBSF values for 14 and 35 day steaks were higher (P < 0.05) than all other treatments. Conversely, 49, 56, and 63 day steaks had higher (P < 0.05) raw L* (lightness) values than 14 and 28 day steaks. Furthermore, 14, 28, 35, and 49 day steaks resulted in higher a* (redness) values (P < 0.05) compared to the 70 day treatment. Also, 70 day steaks had a higher (P < 0.05) percentage of MMb than the 28 day treatment, as well as a higher (P < 0.05) OMb percentage than both 49 and 56 day steaks. The Bottom Line: This research indicates extended aging improves tenderness and overall liking while not decreasing flavor for consumers, which supports using extended aging periods for historically tough muscles.
Keywords: beef; extended aging; palatability